A renal mycosis of roach (Rutilus rutilus) caused by the Aureobasidium pullulans - Řehulka, Jiří; Hubka, Vit (Medical mycology case reports, 2024)
Spontaneous mycosis caused by Aureobasidium pullulans is documented in roach in a cyprinid-prevalent water reservoir in Czechia. Gross pathological lesions included pale gills and splenomegaly, as revealed during necropsy examination. Histological examination showed extensive foci with fungal elements in the kidney. The isolated fungus was identified through phenotypic and molecular characterization, including phylogeny. This report represents the first case of A. pullulans infection in fish and cold-blooded vertebrates, to the best of our knowledge.
Keywords: Molecular diagnosis; Black yeasts; Histopathology; Spontaneous mycosis; Nuclear erythrocyte abnormalities